1981
DOI: 10.1111/j.1365-2672.1981.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Activity and the aw Controlling Solute on Spore Germination of Bacillus stearothermophilus

Abstract: The germination of spores of Bacillus stearothermophilus was studied in nutrient broth in relation to the water activity (a,.,) of the medium, the nature of the a, controlling solutes glycerol, sucrose, KCI, and NaCI, and temperature. Quantitation of germination was based on the change of the phase-bright spore to phase-dark. Activation of spores was by exposure to 100°C/10 min in a medium of the same composition as that used for germination.Of the four solutes used, sucrose proved most inhibitory to germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The mechanical mechanism proposed here for altering shape between spiral and non-spiral forms could be operating in many types of cells that are helically wound with stretch-resistant or contractile fibers. For example, the mechanism we propose can explain why curved-rod bacteria such as C. crescentus (Fischer et al 2002, Wortinger et al 1998 and V. cholerae (Buddelmeijer et al 2002) become spirals as they lengthen when starved, and why multicellular filaments of many species of bacteria wrap around themselves to form supercoiled structures (Anagnostopoulus and Sidhu 1979, Hernandez-Muniz and Stevens 1988, Janssen et al 1991, Mendelson 1976, Mendelson et al 1995.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mechanical mechanism proposed here for altering shape between spiral and non-spiral forms could be operating in many types of cells that are helically wound with stretch-resistant or contractile fibers. For example, the mechanism we propose can explain why curved-rod bacteria such as C. crescentus (Fischer et al 2002, Wortinger et al 1998 and V. cholerae (Buddelmeijer et al 2002) become spirals as they lengthen when starved, and why multicellular filaments of many species of bacteria wrap around themselves to form supercoiled structures (Anagnostopoulus and Sidhu 1979, Hernandez-Muniz and Stevens 1988, Janssen et al 1991, Mendelson 1976, Mendelson et al 1995.…”
Section: Discussionmentioning
confidence: 90%
“…However, certain strains, or mutants, of some species form chains of cells that do not separate upon replication. These multicellular filaments, under particular growth conditions, take on a spiral form and wrap around themselves to produce super-coiled structures reminiscent of tangled telephone cords; examples are Bacillis subtilis (Mendelson 1976, Mendelson et al 1995, Bacillus stearothermophilus (Anagnostopoulus and Sidhu 1979), Mastigocladus laminosus (Hernandez-Muniz and Stevens 1988) and Thermus sp. (Janssen et al 1991) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol can act as an exogenous source of compatible solute that enters the cell and reduces the physiological impact of low water availability. In studies of bacterial spore germination, Anagnostopoulos & Sidhu 1981 and Botha & Holzapfel 1988 found that glycerol favoured germination at reduced a w relative to NaCl. This suggests that exogenous glycerol can enhance germination of microbial propagules at reduced a w .…”
Section: Methodsmentioning
confidence: 99%
“…The influence of water activity-depressing solute like NaCl on the thermal resistance of microorganisms such as those observed in this study is similar to those of Coroller, Leguérinel, and Mafart (2001) who reported increased thermal resistance of Bacillus cereus spores in suspending medium containing solutes. Anagnastopoulos and Didhu (1981) and Coroller et al (2001) explained that the presumed protective mechanism rendered by solutes to spores is through the inhibition of spore germination during heating. Since hydration of spore is an important requisite of activation and germination, the presence of water-binding solutes prevents spores from germinating into the more sensitive vegetative cells during heating.…”
Section: Effects Of Ph and Nacl On Heat-sensitizing Property Of Licormentioning
confidence: 98%